GRASPING SPATIAL SOLUTIONS IN DISTRIBUTED DYNAMIC WORLDS - Sapaty, Peter Simon (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
A high-level ideology and technology will be revealed that can effectively convert any distributed system (manned, unmanned or mixed) into a globally programmable spatial machine capable of operating without central resources. Compact mission scenarios in a special high-level language can start from any point, runtime covering & grasping the whole system or its parts needed, setting operational infrastructures, and orienting local and global behavior. The approach offered can be particularly useful for quick reaction on asymmetric situations and threats the world is facing, paving the way to massive use of cooperative robotics and gradual transition to unmanned systems for solving critical problems in unpredictable environments